Riverine dissolved lithium isotopic signatures in low‐relief central Africa and their link to weathering regimes. Issue 9 (6th May 2016) - Henchiri, Soufian; Gaillardet, Jérôme; Dellinger, Mathieu; Bouchez, Julien; Spencer, Robert G. M.
Abstract: The isotopic composition of dissolved lithium (δ 7 Li) near the Congo River mouth varied from 14‰ to 22‰ in 2010 and was negatively correlated to discharge. From the relationship between dissolved δ 7 Li and strontium isotopes, we suggest that this large variation is due to mixing of waters from two contrasting continental weathering regimes. One end‐member (high δ 7 Li ≈ 25‰) represents waters sourced from active lateritic soils covering the periphery of the basin (Li highly sequestered into secondary mineral products) and another representing blackwater rivers (low δ 7 Li ≈ 5.7‰) derived from the swampy central depression where high organic matter content in water leads to congruent dissolution of the Tertiary sedimentary bedrock. This suggests that the lithium isotopic signature of tropical low‐relief surfaces is not unique and traces the long‐term, large‐scale vertical motions of the continental crust that control geomorphological settings. This evolution should be recorded in the oceanic secular δ 7 Li curve. Key Points: Dissolved Li isotope composition at mouth of the Congo River is controlled by hydrologic mixing Two contrasting dissolved δ 7 Li values in the Congo reveal two distinct weathering regimes Low late Paleocene seawater δ 7 Li value is not unequivocally generated by flat continents